Ecopedagogics of Manggarai Belis Culture: Efforts to Preserve the Symbolic Relationship Between Humans and Nature to Prevent the Commodification of Local Culture - Femberianus Sunario Tanggur; Tri Marhaeni Pudji Astuti; Moh Shole; Fredy Hermanto; I Gede Wayan wisnuwardana; Nuryanti Nuryanti; Edwin Mirzachaerulsyah (Universitas Negeri Gorontalo, 2025)
Local culture shapes the ecological ethics of society, but globalization and commodification often erode its symbolic and ecological meaning. The Belis tradition in Manggarai Regency, East Nusa Tenggara, which is rich in spiritual and ecological values, is now undergoing changes due to modernization. The purpose of this study is to analyze the role of eco-pedagogy in preserving the symbolic relationship between humans and nature through the Belis tradition, identify ecological values, the impact of commodification, and formulate education strategies based on local wisdom. Using a qualitative approach with a case study method, data was collected through interviews, participatory observation, and documentation studies. Thematic analysis was conducted to examine human-nature relations, ecological values, and cultural commodification, with triangulation of sources and member checking for data validity. The results of this study show that the Belis tradition is not only a social and cultural practice, but also functions as a medium for ecological education that instills awareness of the sacred relationship between humans, livestock, and nature. However, the commodification of Belis culture, which has turned livestock into mere economic symbols, has threatened the ecological and spiritual values of this tradition. This research contributes to the development of a local wisdom-based education model for maintaining the relationship between humans and nature. Further research should explore the role of the younger generation in preserving the ecological values of the Belis tradition and formulate an applicable eco-pedagogical model in the context of Manggarai education